Household debt, corporate debt, and the real economy: Some empirical evidence - Donghyun Park; Kwanho Shin; Shu Tian (Asian Development Bank (ADB), 2018)
The rapid accumulation of private debt is widely viewed as a major risk to financial and economic stability. This paper systematically and comprehensively assesses the effect of private debt buildup on economic growth. In the spirit of Mian, Sufi, and Verner (2017) that separately examine the effects of two types of private debt, i.e., household debt and corporate debt, on growth in developed economies, this study specifically provides new evidence on the growth - private debt nexus in both advanced and emerging market economies (EMEs). Moreover, we construct financial peaks in terms of the speed of debt accumulation rather than crisis dates and find that in both advanced and EMEs, corporate debt buildups cause more financial peaks than household debt buildups. Further, corporate debt-induced financial recessions inflict a bigger damage on output than household debt-induced financial recessions in EMEs. Overall, our evidence suggests that policy makers would do well to closely monitor not only household debt but also corporate debt.
Keywords: E32; E44; G01; 330; business cycle; corporate debt; crisis; debt; economic growth; household debt; output; private debt